Endovascular treatment of high-flow priapism using a combination of embolic materials: A case report and a review of the literature - Lucarelli, Nicola Maria; Villanova, Ilaria; Lorusso, Giovanni; Ciccarese, Giorgio; Mirabile, Alesssandra; Maggialetti, Nicola; Stabile Ianora, Amato Antonio (Acta Biomedica Atenei Parmensis, 2026)
Priapism is a pathological condition defined as a prolonged and often painful erection, unrelated to sexual stimulation, that persists more than 4 hours. It is generally classified into different types based on its etiology and pathophysiology.High-flow (non-ischemic) priapism is a rare condition and typically results from perineal or penile trauma, which can lead to the formation of an arteriovenous fistula.This report details a case of high-flow priapism treated successfully with superselective arterial embolization, highlighting the diagnostic process, therapeutic approach, and follow-up outcomes. We present the case of a 29 years-old male patient admitted to the hospital after bicycle trauma that occurred 24 hours earlier. Doppler ultrasound was performed and revealed a left-sided arteriovenous fistula. Selective catheterism of the left internal iliac artery showed an arteriovenous fistula fed by left pudendal artery, so a superselective microcatheterism was performed to reach the site of fistula. Transcatheter arterial embolization was carried out using gelatin sponge followed by the deployment of two detachable microcoils. Doppler ultrasound was repeated 24 hours after the embolization procedure, demonstrating a significant reduction of arteriovenous fistula with minimal residual flow, which wasn’t deemed clinically significant. In the days following the procedure, the symptoms resolved completely, and the patient was discharged with neither recurrences nor complications. Endovascular embolization is safe and effective in the treatment of the high-flow non-ischemic priapism, offering a low rate of complications, short recovery time, and successful resolution of symptoms, preserving erectile function.